UNDERSTANDING THE INTRICACIES OF STUDENT PSYCHOLOGY AND NAVIGATING THE COMPLEX LANDSCAPE OF LEARNING PROCESS - Saparova Liza Kalmuratovna (Journals Park Publishing, 2023)
The realm of student psychology is a fascinating and intricate landscape that plays a pivotal role in shaping the educational experience. Students, at various stages of their academic journey, grapple with a multitude of emotions, challenges, and aspirations that significantly impact their learning outcomes. This article delves into the diverse facets of student psychology, exploring the cognitive, emotional, and social dimensions that contribute to the complex tapestry of the student mind.
Keywords: Student Psychology, Cognitive Processes, Emotional Well-being, Social Dynamics, Educational Technology, Transition Periods, Student Engagement, Professional Development.